Distance, envisaging clouds of phantom - Chong, Keith Jie Hua (2015)
Our understanding and visualizing of the world is bounded within the limitation of our sight, anything beyond our perceptible vision is all in blur.Our perception is divided into two different worlds. The proximal view – speaks with clarity and truth, while in the distant – it is clouded by phantoms where reality hindered by our fantasies. My interest is to extend the ability to see beyond our limitation, uncovering the truth amongst the phantoms, in hope to unfold new perspective and insight to life.Distance = beyond present experience = future /space = mental. A study of psychological distance – My project aims to expand our knowledge on the different dimensions of distance and how it affects the way we think. Through this we become more aware about distance and how it empowers us with the ability to discern fiction from reality.